DYNAMICS OF FRUIT FLIES POPULATIONS IN TWO MANGO PRODUCTION ZONES (KORHOGO AND FERKÉ) IN NORTHERN CÔTE D’IVOIRE - Yves, Minhibo Magloire; Moïse, Akpesse Akpa Alexandre; Tenon, Coulibaly; Hervé, Koua K; Adama, Coulibaly (International Journal of Research -GRANTHAALAYAH, 2019)
Fruit flies are a major constraint to the production and export of mangoes by causing the rot of mangoes. The objective of this work is to follow the fluctuation of population of flies in the northern part of Côte d'Ivoire between May 2015 and October 2016. A network of trapping flies using food baits (the Torula and Ceratrap) and sexual attractants (Methyl Eugenol and Trimedlure) were set up in Korhogo and Ferké mango orchards with the forest Diabaté Kamonon and the forest Petit Clerc as reference area. During trapping, 11 species of fruit flies were identified at all study sites. Among these species, Bactrocera dorsalis and Ceratitis cosyra, were the most abundant in the area. In general, diversity indices were low. The Ferké’s Forest has the highest Shannon index (H = 1.20). This index was higher than the index found in Ferke's orchards (0.9398). At Korhogo the Shannon index in orchards (H = 0.84) is higher than in the forest (H = 0.41). It has been observed that the genus Bactrocera swarmed on mango orchards when precipitation was plentiful. While the genus Cerartitis only appeared when precipitation was low. In addition, knowledge of the ecology and fluctuation of fruit flies, will allow to develop a site monitoring device through a trapping system with sexual and food attractants.